Twitter (X) and the Commercial Determinants of Health: Characterizing the Most Amplified, Influential, and Connected Voices Driving Twitter Discourse About Tobacco Regulatory Policy From September 2019 to July 2021 - Nathan A. Silver; Miao Feng; Elexis C. Kierstead; Hy Tran; Steven Binns; Sherry Emery; Barbara A. Schillo (Social Media + Society)
Tobacco content on Twitter (X) generally opposes regulation. Although a near real-time data source of the public’s response to prominent events heightens the allure of extrapolating public sentiment from Twitter content, tobacco policy sentiment on the platform may be more indicative of industry-affiliated top users. We examined 2 years of tobacco policy discussion on Twitter (X) at the user level ( N  = 3,159,807 posts) from September 2019 to July 2021. We sampled the 100 most followed, amplified (retweets), influential (H index), and connected (betweenness centrality) users at three different time periods: pre-COVID (September 2019 to February 2020), COVID lockdown (March 2020 to March 2021), and post vaccine rollout (April to July 2021) to characterize top users. The Louvain method was used to partition users into communities based on retweet behavior. The 100 most amplified users received between 48% and 71% of all retweets across time periods, with e-cigarette advocates dominating the most amplified (64.7%), influential (38.4%) and connected users (42.1%). The vast majority of interaction took place in communities dominated by e-cigarette advocates, but only reaching 2.5% to 8.2% of users. We identified 58 tobacco policy top users who had 1,000 or more total retweets and were among the top 100 for any of our influence metrics at more than one time period. Among top users, 50 were e-cigarette advocates, and 24 had quantifiable ties to the tobacco industry. Practitioners and researchers should be wary of mischaracterizing industry public relations on social media as public sentiment.